1992
DOI: 10.1111/j.1472-765x.1992.tb00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Some rumen bacteria degrading fructan

Abstract: Degradation of fructan obtained from timothy (Phleum pratense L.) by the following six species of bacteria isolated from sheep rumen was studied: Streptococcus bovis, Bacteroides ruminicola, Selenomonas ruminantium, Butyrivibrio fibrisolvens, Treponema bryantii and Treponema saccharophilum. The enzymatic activity of the bacteria was analysed by TLC. The highest activity was found in whole cells and in the strains B. fibrisolvens No. 3 and T. saccharophilum S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 9 publications
1
39
0
2
Order By: Relevance
“…All chemicals were of analytical grade. Timothy grass fructan was isolated and purifi ed according to Ziołecki et al (1992).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…All chemicals were of analytical grade. Timothy grass fructan was isolated and purifi ed according to Ziołecki et al (1992).…”
Section: Chemicalsmentioning
confidence: 99%
“…However, neither fructanolytic species of rumen microbiota nor their enzymes involved in degradation of fructose polymers in this highly specifi c ecosystem have been well recognized to date. The previous investigation carried out at our laboratory showed that some strains of rumen treponemes were presumably able to synthesize β-fructofuranosidase (Ziołecki et al, 1992;Guczyńska, 1999). Further studies revealed, however, that strain S of these microorganisms synthesized a specifi c endolevanse and unspecifi c β-fructofuranosidase (Kasperowicz and Michałowski, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To be useful as a food source, any fructan must be metabolized at rates commensurate with the rate of passage through the rumen and must be linked to the utilization of ammonia from protein metabolism within the rumen. Although the degradability of some plant fructans by isolated rumen bacteria and protozoa has previously been reported (Anand, 1972; Paster and CanaleParola, 1985;Thomas, 1960;Ziolecki et al, 1992), there is no information on either the overall rate of inulin digestion or the degradability of the large bacterial levans within the rumen. Nor has the effect of levan or inulin on NH 3 metabolism in the rumen been reported.…”
mentioning
confidence: 99%
“…Butyrivibrio fibrisolvens strain 3 bacteria isolated from ovine rumen (Ziołecki et al, 1992) were cultured in an anaerobic medium (Hungate, 1969) supplemented with 0.5% (w/v) of timothy grass fructan, inulin, inulo-oligosaccharides, sucrose, or fructose as the sole source of energy. The bacteria were grown for 24 h. At the end of the incubation period, the optical density of the cultures was determined by measuring absorbance at 660 nm and the carbohydrate concentration in the medium was determined by the anthrone method.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, very little is known about the ability of these bacteria to utilize fructans (Ziołecki et al, 1992), which are important storage carbohydrates in grasses and Compositae and consist of fructofuranosyl residues linked by either β-2,6 (levans) or β-2,1 (inulins) glycosidic bonds. The objective of this study was, therefore, to examine the ability of B. fibrisolvens to utilize various fructose polymers.…”
Section: Introductionmentioning
confidence: 99%